The relationship between financial sector development and economic growth: the case of Zambia - Mwachande, M'khuzo (Graduate School of Business (GSB), 2026)
This study examines the relationship between financial sector development and economic growth in Zambia, focusing on the roles of financial sector growth, bank efficiency, human capital, and institutional quality. Given Zambia's ongoing financial reforms, the research aims to fill the gap in understanding how these factors influence economic performance, particularly in the short and long term. The problem addressed by the study is the unclear impact of financial sector reforms on economic growth, despite substantial progress in financial sector development. The study's objectives were to estimate the short- and long-run relationships between financial sector development and economic growth, analyse the effect of bank efficiency on financial sector development, and explore the moderating influence of human capital and institutional quality. The results, derived from the ARDL model, indicate that financial sector development has a positive long-term relationship with economic growth, with no significant short-term effects. While improvements in bank efficiency were found to be positively associated with financial sector development in the long run, no substantial short-term impact was observed. Human capital and institutional quality did not show significant effects on economic growth or bank efficiency, suggesting that these areas need further development for full economic benefits. The study concludes that while financial sector development plays a critical role in driving long-term economic growth, improvements in human capital and institutional quality are necessary to enhance the sector's effectiveness. The findings offer valuable insights for policymakers seeking to strengthen Zambia's financial sector and achieve sustainable economic growth. Further research is recommended to explore the delayed effects of financial reforms, the role of financial technology, and the impact of institutional quality on economic outcomes.